Growth, Mortality and Yield per Recruit of Johnieops vogleri (Bleeker) from Mumbai Waters - S. K., Chakraborty; R. S., Biradar; A. K., Jaiswar; R., Palaniswamy (Fishery Technology, 2025)
Growth, mortality and yield-per-recruit of sharp toothed hammer croaker, johnieops vogleri (Bleeker) is studied. Loo and K were estimated as 374 mm and 0.73/year. Z, M and F were estimated as 4.13, 1.27 and 2.86 respectively. The length at first capture was 170 mm. Phi prime was calculated as 6.94. This species with Z/K ratio of 5.65 has high mortality. The yield isopleth diagram shows that optimum yield can be obtained at Lc/ Loo value of 0.45 and E of 0.65. This shows that the fish belongs to quadrant "C" of ’yield isopleth’ diagram where fishery is well developed and large sized fish can be caught at higher efforts. However, it may deplete the stock. Thus in order to sustain the catch, it is better to continue fishing at the present level of efforts